50 Years in the World of Oil – Memoirs and Autobiography – 50. Issue 2 (1st September 2019) - Jiyad, Ahmed Mousa
50 Years in the World of Oil – Memoirs and Autobiography – 50Issam Al-Chalabi (2019)Beirut/Lebanon: Arab Establishment for Studies and Publications, 820 pp., ISBN 978-6-14419-945, h/bk